Analisis Hubungan Indeks Ketahanan Pangan dan Presentase Kemiskinan di Jawa Tengah dengan Korelasi Kendall Tau - Novita Eka Chandra; Melda Juliza; Abdul Aziz; Ari Wardayani (Mathematics Department, Faculty of Sciences and Technology Unisda Lamongan, 2026)
Food security and poverty are two important economic indicators that are interrelated and are a primary focus of the Sustainable Development Goals (SDGs). This study aims to analyze the strength and direction of the relationship between the Food Security Index (IKP) and the percentage of district/city poverty in Central Java Province from 2022 to 2025. The data used do not meet the assumption of a normal distribution and have several identical values (ties), so the analysis method used is the Kendall Tau correlation. The results show a significant negative relationship between the IKP and the percentage of poverty in Central Java. These results indicate that the IKP at the district/city level plays a role in reducing the percentage of poverty.